Quantification of vertical transmission of Neospora caninum in dairy cows in Minas Gerais, Brazil - Santos,Raquel Ribeiro Dias (2012)
The objective of this cross-sectional study was to estimate the rate of vertical transmission and to investigate horizontal transmission of Neospora caninum and occurrences of reproductive abnormalities in seropositive dairy cows on two farms in the state of Minas Gerais, Brazil. The frequency of cows seropositive for N.caninum according to the indirect fluorescent antibody test (IFAT) was 39.4% (93/236) for Farm A and 31.4% (32/102) for the Farm B (p > 0.05). The mean vertical transmission rates for N. caninum were 29% and 9% for the herds of Farms A and B, respectively. No negative effects (p > 0.05) from infection by N.caninum were observed regarding milk production and occurrences of reproductive abnormalities in herds A and B.